With God on our side: Christianity, whiteness, Islam and otherness in the Australian experience. Issue 6 (1st November 2016) - Stratton, Jon
Abstract: This article discusses the whiteness of Christianity in Australia and the ways that Islam has been constructed as Other. Its starting point is the phrase used by a protestor at a Reclaim Australia event: 'Jesus not Islam'. The article begins with a historical contextualization showing how Christianity became white in Europe from around the early seventeenth century. It then discusses how Islam came to be produced as a fundamental threat to Christianity, the moral order articulated through it, and the civilization built on it. The article argues that recognizing this is a necessary foundation for understanding why Islam has been singled out in Australia and the ways that the 'Australian Muslim' has been constructed.